Effect of Postdeposition Annealing on the Structural and Sensing Characteristics of Tb2O3 and Tb2Ti2O7 Sensing Films for Electrolyte-Insulator-Semiconductor pH Sensors. Issue 4 (3rd February 2015) - Pan, Tung-Ming; Wang, Chih-Wei; Huang, Yu-Shu; Weng, Wen-Hui; Pang, See-Tong
Abstract : In this study, we proposed an electrolyte–insulator–semiconductor (EIS) device fabricating from Tb2 O3 and Tb2 Ti2 O7 sensing films deposited on Si substrates through reactive sputtering. The effect of different annealing temperatures (600, 700, 800, and 900°C) on the structural and surface properties of the Tb2 O3 and Tb2 Ti2 O7 sensing films was investigated. The performance of the Tb2 O3 and Tb2 Ti2 O7 sensing films as pH sensors was evaluated and correlated with the observed material properties. Compared with the Tb2 O3 sensing film, the EIS sensor using the Tb2 Ti2 O7 sensing film that had been annealed at 900°C exhibited better pH sensing performances, including a higher sensitivity (69.21 mV/pH), a smaller hysteresis voltage (4 mV), and a lower drift rate (0.113 mV/h), presumably the incorporation of Ti into the Tb2 O3 to form a well-crystallized Tb2 Ti2 O7 structure.